A Rare Case of Primary Amenorrhea with Two Etiologies, Hypothalamic Amenorrhea, Transverse Vaginal Septum, and No Hematocolpos - Firouzeh Ghaffari; Fatemeh Keikha; Arezoo Arabipoor (Case Reports in Obstetrics and Gynecology)
We reported a rare case of hypothalamic amenorrhea and transverse vaginal septum. A 28-year-old woman presented with primary amenorrhea and no complaint of abdominal pain. Laparoscopy revealed a small rudimentary uterus with streak ovaries and a vaginal pouch. The patient with diagnosis of Mayer-Rokitansky-Kuster-Hauser (MRKH) syndrome was subjected to a vaginoplasty in another fertility center. In our institute, after two courses of estrogen and progesterone, sonography revealed hematocolpos, while, under anesthesia, transverse vaginal septum was resected. Hysteroscopy revealed normal uterine cavity. She became pregnant 5 months postoperatively with controlled ovarian stimulation (COS) in conjunction with intrauterine insemination, and she has two healthy babies now. This case highlights the importance of careful evaluation of all primary amenorrheas. Clinicians should be aware of presence of more than one etiology which causes atypical presentations and accomplishes a systematic strategy for the evaluation of amenorrhea potential to avoid long-term side effects of a misdiagnosis.